Characterization of transient response in fiber grating Fabry–Perot lasers - Adikan, Faisal Rafiq Mahamd; Hisham, H.K.; Mahdiraji, G.A.; Abas, A.F.; Mahdi, M.A. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
A comprehensive study on the transient response of fiber-grating Fabry–Perot(FGFP) laser is numerically conducted. Fiber Bragg grating (FBG) is used as a wavelength selective element to control the external optical feedback (OFB) level. In addition to the external OFB level, the effect of other external cavity parameters such as temperature, injection current, dc-bias level, coupling coefficient, and gain compression factor on transient response characteristics of the laser are investigated. The temperature dependence(TD) of response characteristics is calculated according to TD of laser parameters instead of well-known Pankove relationship. Results show that, by increasing the laser injection current, the relaxation oscillation’s amplitude, frequency, and damping rate are increased, while the laser turn-on time delay is reduced. In addition to the injection current and dc-bias level, the turn-on time delay can be reduced by increasing OFB reflectivity. It is shown that the optimum external fiber length (Lext) is 3.1 cm and the optimum range of working temperature for FGFP laser is within ±2° C from the FBG reference temperature (To). Also, it is shown that antireflection (AR) coating facet reflectivity value of 1 × 10-² is sufficient for the laser to operate at good response characteristics with low fabrication complexity.